2014
DOI: 10.1039/c4sm01219d
|View full text |Cite|
|
Sign up to set email alerts
|

Cholesterol solubility limit in lipid membranes probed by small angle neutron scattering and MD simulations

Abstract: The solubility limits of cholesterol in small unilamellar vesicles made of POPS and POPC were probed using Small Angle Neutron Scattering (SANS) and coarse grained (CG) molecular dynamics (MD) simulations. SANS, being non-invasive, allowed the direct and quantitative measurement of cholesterol in intact vesicles. Our experimental measurements reveal a 61% mole fraction solubility limit of cholesterol in POPC, consistent with previous studies. However, in POPS the solubility limit of cholesterol is found to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Excess cholesterol can induce severe coronary pathology with the narrowing of the inner blood vessel walls through the deposition of plaques containing cholesterol crystals, which is due to the solubility limit of cholesterol into lipids. A recent SANS study performed on lipid contrast matched conditions to isolate the scattering coming from the cholesterol [ 64 ] inserted in a POPC or POPS liposome, has revealed a molar fraction solubility limit of 61% and 73% of cholesterol in POPC and POPS, respectively. Further, no evidence of stable nanodomains of cholesterol in POPS membranes was found, as suggested in other reports.…”
Section: Sans For the Characterization Of Liposome Nanocarriersmentioning
confidence: 99%
“…Excess cholesterol can induce severe coronary pathology with the narrowing of the inner blood vessel walls through the deposition of plaques containing cholesterol crystals, which is due to the solubility limit of cholesterol into lipids. A recent SANS study performed on lipid contrast matched conditions to isolate the scattering coming from the cholesterol [ 64 ] inserted in a POPC or POPS liposome, has revealed a molar fraction solubility limit of 61% and 73% of cholesterol in POPC and POPS, respectively. Further, no evidence of stable nanodomains of cholesterol in POPS membranes was found, as suggested in other reports.…”
Section: Sans For the Characterization Of Liposome Nanocarriersmentioning
confidence: 99%
“…More recently, we found how defects in membrane packing induced by a supporting surface facilitate lipid flip-flop too and methodologies that can potentially have this effect on membranes result in inaccurate measured rates ( 39 ). From the MD side, we have also suggested that the tendency of the simulations to accumulate cholesterol in the bilayer center suggests that the energy barrier to flip is too low ( 46 , 47 ). Further, with TR-SANS, we have demonstrated that although exchange and flip-flop are coupled, it is their interdependence in the movement of lipids between and within membranes that allows for their distinction, even when the most significant contribution in TR-SANS comes from the exchange process as supported by the AIC test.…”
Section: Discussionmentioning
confidence: 94%
“…To conclude, we reiterate that the proposed hypothesis has already been tested in its basic sense. The published experimental results show that (1) formation of CBDs in liposomal membranes precedes formation of Chol crystals (e.g., [ 17 , 18 , 20 , 30 , 31 ]), and (2) Chol crystals can be formed from membrane Chol (without the external addition of Chol) when the Chol solubility threshold in the membrane is decreased, for example, by lipid peroxidation [ 21 23 ]. Based on the saturation recovery EPR technique, we are planning to design an experimental procedure to quantitatively estimate the average amount of Chol in a CBD at the saturation threshold in bilayers made of polyunsaturated phospholipids (before peroxidation).…”
Section: Discussionmentioning
confidence: 99%
“…When the amount of Chol in a membrane exceeds the saturation limit, Chol bilayer domains (CBD) form in the membrane [17]. A further increase of Chol content above the Chol solubility threshold induces formation of Chol crystals [17][18][19][20]. The peroxidation of phospholipids in a membrane containing a large amount of Chol does not change the relative proportion of Chol and phospholipids; however, it lowers the amount of Chol needed for CBDs to start to form [21][22][23].…”
Section: A New Hypothetical Pathway Leading To the Formation Of Cholementioning
confidence: 99%
See 1 more Smart Citation